Leonurine Improves Age-Dependent Impaired Angiogenesis: Possible Involvement of Mitochondrial Function and HIF-1α Dependent VEGF Activation - Jia Qi; Jia Qi; Jing J. Wang; Jun L. Duan; Zhao Y. Lu; Yang G. Yuan (Frontiers in Pharmacology, 2017)
Objective: Advanced age is associated with impaired angiogenesis in part because of mitochondrial dysfunction. We have recently reported that leonurine exerts protective effects in neuron via regulation of mitochondrial function. The aim of this study was to explore whether leonurine is able to attenuate mitochondrial dysfunction and to enhance angiogenesis in old rats with hindlimb ischemia.Methods and Results: At day 14 after surgery, hypoxia-inducible factor (HIF)-1α and vascular endothelial growth factor (VEGF) expression was decreased in the ischemic muscle of aged animals, which was accompanied by enhanced oxidative stress, increased mitochondrial damage, decreased capillary density, and reduced limb perfusion compared with young mice. Importantly, these effects were inhibited by leonurine treatment in old animals. In vitro, we showed that the functional activities (migration and tube formation) of human umbilical vein endothelial cells (HUVECs) were significantly impaired in senescent compared to young. However, leonurine rescued HUVECs functional activities in senescent HUVECs. Mechanistically, we found that leonurine restored the age-dependent reduction in HIF activity and subsequent reduced VEGF expression in senescent HUVECs. Moreover, the mitochondrial oxidative stress was significantly augmented in senescent HUVECs, in association with reduced mitochondrial function. However, leonurine significantly reduced the mitochondrial oxidative stress and restored the mitochondrial membrane potential.Conclusion: Our results demonstrate that leonurine protects against age-dependent impairment of angiogenesis possibly through attenuation of mitochondrial dysfunction and subsequent VEGF up-regulation impairment.